A Community-Based Intervention Program to Enhance Family Communication and Family Well-being: The Learning Families Project in Hong Kong - Shen, Chen; Wan, Alice; Kwok, Lit Tung; Pang, Sally; Wang, Xin; Stewart, Sunita M.; Lam, Tai Hing; Chan, Sophia Siu Chee (Frontiers in Public Health, 2017)
Background: Family communication is important to maintain family relationships and family well-being. To enhance family communication and family well-being, a community-based “Learning Families Project”, based on the social ecological model was developed in Kwun Tong in Hong Kong, a district with high prevalence of family problems. Methods: This quasi-experimental study included two nearby government subsidized low-rent housing estates separated by busy main roads, as the intervention (Tsui Ping (South) Estate) and control (Shun Tin Estate) estate. The main intervention was resident training programs, such as talks, day camps and thematic activities. No program was implemented in the control estate. Participants in the intervention group received assessments before the intervention (T1), immediately after the intervention (T2), and 6 weeks after the intervention (T3). Control group participants were assessed at baseline (March to April 2011) and follow-up (December 2011 to March 2012). Assessments of family communication (time and perceived adequacy) and family well-being (harmony, happiness and health) at T1 and T3 were obtained in the intervention group to examine within-group changes. In addition, these differences in outcomes in the intervention group were compared with those in the control group to examine the effectiveness of the intervention. Results: Family communication time and perceived communication adequacy increased significantly in the intervention group (n=515) with a small effect size (Cohen effect d: 0.10 and 0.24, respectively). Compared with the control group (n=476), the improvements in family communication time and perceived communication adequacy (Cohen effect d: 0.13 and 0.14, respectively), and perceived family harmony and happiness (Cohen effect d: 0.12 and 0.12, respectively) were significantly greater in the intervention group, adjusting for age and education, suggesting the intervention was effective in improving family communication and family well-being. Mediation analysis showed that perceived communication adequacy mediated the effects of the intervention on family harmony (β=0.10, 95% CI 0.03, 0.18), happiness (β=0.12, 95% CI 0.04, 0.20) and health (β=0.10, 95% CI 0.02, 0.17), adjusting for age and education. Conclusions: This community intervention based on the social ecological model improved family well-being through improving family communication, which could be an effective target to promote family well-being in other communities.